Rehabilitating Occlusion with a Guiding Flange Prosthesis in a Patient with Mandibular Resection: A Case Report - Abhilash Mohapatra (Indian Journal of Forensic Medicine & Toxicology, 2020)
Defects with the discontinuity of the mandible following a segmental mandibulectomy present a majorchallenge for rehabilitation. These challenges include correction of deranged mandibular movements,disfigurement, and esthetics, correction of functional difficulty seen during swallowing,speech andarticulation, and also of surgical side deviation of the remainder mandibular structure. The following casereport elaborates on the prosthodontic rehabilitation of a patient with the help of a device named «GuideFlange Prosthesis»which isindicated to correct such manifestations seen after hemimandibulectomy